Comparison of Acute Recoil between Bioabsorbable Poly-L-lactic Acid XINSORB Stent and Metallic Stent in Porcine Model. (3rd October 2012) - Wu, Yizhe; Shen, Li; Wang, Qibing; Ge, Lei; Xie, Jian; Hu, Xi; Sun, Aijun; Qian, Juying; Ge, Junbo
Abstract : Objective . To investigate acute recoil of bioabsorbable poly-L-lactic acid (PLLA) stent. Background . As newly developed coronary stent, bioabsorbable PLLA stent still encountered concern of acute stent recoil. Methods . Sixteen minipigs were enrolled in our study. Eight PLLA XINSORB stents (Weite Biotechnology Co., Ltd., China) and eight metallic stents (EXCEL, Jiwei Co., Ltd. China) were implanted into coronary arteries. Upon quantitative coronary angiography analysis, acute absolute recoil was defined as the difference between mean diameter of inflated balloon ( X ) and mean lumen diameter of stent immediately after deployment ( Y ), while acute percent recoil was defined as ( X−Y )/ X and expressed as a percentage. Intravascular ultrasound (IVUS) was performed immediately after implantation and 24 hours later to compare cross-sectional area (CSA) between two groups and detect stent malapposition or collapse. Results . Acute absolute recoil in XINSORB and EXCEL was0.02 ± 0.13  mm and −0.08 ± 0.08  mm respectively (P = 0.19 ). Acute percent recoil in XINSORB and EXCEL was0.66 ± 4.32 % and −1.40 ± 3.83 %, respectively (P = 0.45 ). CSA of XINSORB was similar to that of EXCEL immediately after implantation, so was CSA of XINSORB at 24-hours followup. Within XINSORB group, no difference existed between CSA after implantation and CSA at 24-hours followup. No sign of acute stent malapposition was detected by IVUS. Conclusions . The acute stent recoil of XINSORB is similar to that of EXCEL. No acute stent malapposition or collapse appeared in both kinds of stent. This preclinical study was designed to provide preliminary data for future studies of long-term efficacy and safety of XINSORB stent.